Electrophysiological Characterization of Ts6 and Ts7, K(+) Channel Toxins Isolated through an Improved Tityus serrulatus Venom Purification Procedure - Cerni, Felipe A. (MDPI, 2014)
In Brazil, Tityus serrulatus (Ts) is the species responsible for most of the scorpion related accidents. Among the Ts toxins, the neurotoxins with action on potassium channels (α-KTx) present high interest, due to their effect in the envenoming process and the ion channel specificity they display. The α-KTx toxins family is the most relevant because its toxins can be used as therapeutic tools for specific target cells. The improved isolation method provided toxins with high resolution, obtaining pure Ts6 and Ts7 in two chromatographic steps. The effects of Ts6 and Ts7 toxins were evaluated in 14 different types of potassium channels using the voltage-clamp technique with two-microelectrodes. Ts6 toxin shows high affinity for Kv1.2, Kv1.3 and Shaker IR, blocking these channels in low concentrations. Moreover, Ts6 blocks the Kv1.3 channel in picomolar concentrations with an IC(50) of 0.55 nM and therefore could be of valuable assistance to further designing immunosuppressive therapeutics. Ts7 toxin blocks multiple subtypes channels, showing low selectivity among the channels analyzed. This work also stands out in its attempt to elucidate the residues important for interacting with each channel and, in the near future, to model a desired drug.